دراسة تأثير مستخلص بذور الفلفل على الأمراض البكتيرية لنبات البطاطا في منطقة وادي سوف - سعيد, اميرة; شلغوم, مريم; معمري, أميرة; غريسي, أشواق; غريسي, أشواق (University of Eloued جامعة الوادي, 2023)
ue to the possibility of obtaining plant extracts extracted from plants available in the local environment, it is characterized by its low price and its use does not result in resistant insect strains, which prompted it to be tested by studying the effect of the aqueous extract of the pepper plant on the champignon that infects the potato plant, the results indicated that the aqueous extract of the pepper plant Effect in destroying and inhibiting the growth of Champignon and that this effect is directly related to the concentration used.
إنتاج نباتي
Keywords: plant extracts; sweet environment; pepper plant; effect; نبات الفلفل